2020
DOI: 10.1051/epjconf/202023914008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FLiBe thermal neutron scattering on reactivity of molten salt reactor

Abstract: Thermal neutron scattering data has an important influence on the calculation and design of reactor with a thermal spectrum. However, as the only liquid fuel in the Gen-IV reactor candidates, the research on the thermal neutron scattering effect of coolant and somewhat moderator FLiBe has not been carried out sufficiently either experimentally or theoretically. The effect of FLiBe thermal neutron scattering on reactivity of TMSR-LF (thorium molten salt reactor - liquid fuel), TMSR-SF (thorium molten salt react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Scattering of thermal neutrons by moderators has a significant impact on reactor core design. It has been reported that thermal neutron scattering law (TSL) data of graphite have a large sensitivity to effective neutron multiplication factors (keff) of not only HTGRs [1] but also MSRs [2].…”
Section: Introductionmentioning
confidence: 99%
“…Scattering of thermal neutrons by moderators has a significant impact on reactor core design. It has been reported that thermal neutron scattering law (TSL) data of graphite have a large sensitivity to effective neutron multiplication factors (keff) of not only HTGRs [1] but also MSRs [2].…”
Section: Introductionmentioning
confidence: 99%